The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1007/s00775-009-0489-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring metallodrug–protein interactions by mass spectrometry: comparisons between platinum coordination complexes and an organometallic ruthenium compound

Abstract: Electrospray ionisation mass spectrometry was used to analyse the reactions of metal compounds with mixtures of selected proteins. Three representative medicinally relevant compounds, cisplatin, transplatin and the organometallic ruthenium compound RAPTA-C, were reacted with a pool of three proteins, ubiquitin, cytochrome c and superoxide dismutase, and the reaction products were analysed using high-resolution mass spectrometry. Highly informative electrospray ionisation mass spectra were acquired following ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 46 publications
(49 reference statements)
4
76
0
Order By: Relevance
“…Furthermore, mass spectrometric studies have shown highly protein-selective binding of RAPTA-C compared to cisplatin in samples containing protein mixtures, which was attributed to steric and hydrophobic effects. [29] The proclivity for site specific association at defined locations on the nucleosome core implies that histone binding could contribute to the therapeutic activity of RAPTA compounds. In fact, following RAPTA-C treatment of cancer cells, we found that approximately 5 % of the intracellular ruthenium content was associated with chromatin, which indicates that the nucleosome is a possible therapeutic target for this drug (see the Experimental Section).…”
Section: Indazolium Trans-[tetrachloridobis(1h-indazole)ruthenatea C mentioning
confidence: 99%
“…Furthermore, mass spectrometric studies have shown highly protein-selective binding of RAPTA-C compared to cisplatin in samples containing protein mixtures, which was attributed to steric and hydrophobic effects. [29] The proclivity for site specific association at defined locations on the nucleosome core implies that histone binding could contribute to the therapeutic activity of RAPTA compounds. In fact, following RAPTA-C treatment of cancer cells, we found that approximately 5 % of the intracellular ruthenium content was associated with chromatin, which indicates that the nucleosome is a possible therapeutic target for this drug (see the Experimental Section).…”
Section: Indazolium Trans-[tetrachloridobis(1h-indazole)ruthenatea C mentioning
confidence: 99%
“…The enzyme TrxR is attracting growing interest as a target for a variety of metallodrugs [22,27,53]. Both X-ray crystallography and MALDI-MS were used previously to show that several terpyridineplatinum(II) complexes bind to TrxR [22], while various gold complexes have also proven to be potent inhibitors of this enzyme [24][25][26].…”
Section: Thioredoxin Reductase Binding Studiesmentioning
confidence: 99%
“…The poor correlation between the binding to DNA and their cytotoxicity has suggested that Ru(II)-arene PTA (RAPTA) compounds act through a mechanism different from that established for classical platinum anticancer drugs. Hence, it is believed that the interaction of the RAPTA complexes with intracellular or extracellular proteins [13,20,21] may represent their primary mechanism of action.…”
Section: Introductionmentioning
confidence: 99%